Barriers to sustainable innovation adoption: A qualitative investigation of metal additive printing from supply and demand perspectives - Pradipta Chatterjee; Steven Greenland; David Low; Chrystie Watson; Ninh Nguyen (Cleaner Logistics and Supply Chain)
Metal additive printing (MAP) is an innovative manufacturing technology with promising sustainability performance standards, including increased supply chain efficiency and responsiveness. Yet, while MAP offers some sustainable advantages over other manufacturing methods, it faces various barriers to widespread adoption. This study used a qualitative research methodology to generate an in-depth understanding of the perceived barriers to MAP adoption. It explored the perspectives of various stakeholders, including MAP researchers and machine manufacturers (supply side), as well as end users (demand side) via 40 in-depth interviews. Study participant responses were analysed using thematic analysis and NVivo to identify key barrier themes and sub-themes. The findings revealed seven main barrier categories: production constraints, quality and standards, cost, social conservatism, education and skills, bureaucratic inertia, and marketing and distribution. Further analysis of these findings generated a unique framework that depicts MAP adoption barriers from both the supply and demand perspectives. This framework can help researchers, manufacturers and marketers to systematically categorise and evaluate MAP adoption barriers and identify ways to overcome them.